2013
DOI: 10.1007/s00198-013-2434-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass and vitamin D levels in women with a diagnosis of fibromyalgia

Abstract: No differences in BMD were found between patients and controls. As for 25OHD, a lack of its expected summer rise was observed. It is doubtful whether this has any homeostatic consequence. We consider that the association reported in other studies is merely circumstantial, and not due to the intrinsic characteristics of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…Reviewing the titles and abstracts revealed 644 irrelevant papers. Investigating the full texts of the remaining articles [ 1 3 5 14 16 22 23 24 25 26 27 28 29 ], two irrelevant papers [ 22 27 ] were also excluded. Others were quality assessed and entered into the final meta-analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the titles and abstracts revealed 644 irrelevant papers. Investigating the full texts of the remaining articles [ 1 3 5 14 16 22 23 24 25 26 27 28 29 ], two irrelevant papers [ 22 27 ] were also excluded. Others were quality assessed and entered into the final meta-analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The largest sample size (205 cases and controls) was used in the study conducted by Mateos et al [ 25 ] while the Baygutalp study [ 5 ] with 19 cases/controls included the smallest sample size. Both of these studies reported lower blood vitamin D levels in FM patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also assessed BMD in 205 patients with FM and 205 healthy controls using dual absoptiometry. No differences in BMD were evident between the two groups [ 54 ].…”
Section: Fibromyalgia and Vitamin Dmentioning
confidence: 99%
“…In recent years, numerous studies were designed to clear an association between a low level of calciferol and FM, two conditions that were prevalent and also lead to chronic pain. In spite of many efforts, the evidence for an association between them is unconvincing; with no progression in pain when on a vitamin D supplement [ 2 3 4 5 6 7 8 24 ]. Many reports have showed that vitamin D deficiency can be implicated in nonspecific chronic pain or FM, and some trials have advocated a vitamin D supplement for treatment of FM [ 6 7 8 25 ], but others have not confirmed it [ 2 3 4 5 25 26 ].…”
Section: Discussionmentioning
confidence: 99%